Mengantar Hidangan, Merajut Iman: Tradisi Maanta Jambi dalam Cermin Jemaat Perdana - Lia Kris Agustina (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2026)
Amidst the eroding values ??of togetherness, preserving local cultural traditions is crucial for maintaining the social and spiritual identity of the community. This article examines the relevance of the Maanta tradition in Jambi as a reflection of the faith values ??of the early church, as depicted in Acts 2:44-47. The Maanta tradition, a Jambi Malay custom of delivering food in food containers to family, relatives, or neighbors during religious occasions, is not only a form of local wisdom but also a manifestation of solidarity, love, and mutual cooperation. Using qualitative methods through literature review, this research examines the social and theological meaning of the Maanta practice and traces its connection to the principle of Koinonia in the early Christian community. The results indicate that the Maanta tradition embodies values ??of togetherness, social concern, and reciprocity, which align with the life of the early church, who shared, helped, and lived in unity of love. Within the context of contextual theology, the Maanta tradition has the potential to become a means of faith inculturation that connects Christian values ??with local culture. The modern church can learn from the Maanta spirit of living out concrete faith through love and service in a pluralistic society.   Abstrak Di tengah arus globalisasi yang kian mengikis nilai kebersamaan, pelestarian tradisi budaya lokal menjadi penting untuk menjaga identitas sosial dan spiritual masyarakat. Artikel ini membahas relevansi tradisi Maanta di Jambi sebagai cerminan nilai-nilai iman jemaat perdana sebagai gambaran dalam Kisah Para Rasul 2:44-47. Tradisi Maanta, yaitu kebiasaan masyarakat Melayu Jambi mengantarkan makanan menggunakan rantang kepada keluarga, kerabat, atau tetangga pada momen keagamaan, tidak hanya sekedar bentuk kearifan lokal, tetapi juga wujud solidaritas, kasih, dan gotong-royong. Dengan menggunakan metode kualitatif melalui studi pustaka, penelitian ini mengkaji makna sosial dan teologis dari praktik Maanta serta menelusuri keterkaitan dengan prinsip Koinonia dalam komunitas Kristen mula-mula. Hasil kajian menunjukkan bahwa tradisi Maanta memuat nilai-nilai kebersamaan, kepedulian sosial, dan timbal balik yang sejajar dengan kehidupan jemaat perdana yang saling berbagi, membantu, serta hidup dalam kesatuan kasih. Dalam konteks teologi kontekstual, tradisi Maanta berpotensi menjadi sarana inkulturasi iman yang menghubungkan nilai-nilai Kristiani dengan budaya lokal. Gereja masa kini dapat belajar dari semangat Maanta untuk menghidupi iman yang konkret melalui kasih dan pelayanan di tengah masyarakat majemuk.